The Mechanism of Strengthening Islamic Education through the Mappanre Temme Tradition among the Bugis Diaspora Community - Anang Taufik; Ikhwan Aziz Q; Muhammad Saidun Anwar (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Islamic education does not solely take place within formal institutions but also develops through socio-religious practices in society as part of the value internalization process. In this context, local religious traditions can function as contextual non-formal Islamic education media. However, studies examining how the mechanisms of strengthening Islamic education operate within traditional practices remain relatively limited. This study aims to analyze the mechanism of strengthening Islamic education in the Qur’anic completion tradition (Mappanre Temme) among the Bugis community in Sukorahayu Village, East Lampung. This research employs a descriptive qualitative approach with a phenomenological perspective. Data were collected through observation, interviews, and documentation involving religious leaders, customary leaders, families, and community members. The findings reveal that the strengthening of Islamic education in the Mappanre Temme tradition occurs through a value internalization mechanism encompassing the dimensions of aqidah (faith), ibadah (worship), akhlaq (morality), and social values. This mechanism is manifested through Qur’anic recitation as a form of worship praxis, the delivery of paseng as a transmission of moral values, the exemplary role of religious and customary leaders as learning models, and collective community participation as a means of developing social awareness. Furthermore, this tradition remains relevant within the context of the Bugis diaspora community despite facing social dynamics such as modernization and population mobility. Therefore, the Mappanre Temme tradition can be understood as a model of non-formal Islamic education based on local wisdom that operates through culturally embedded value internalization mechanisms in community life.